Peran Kepala Sekolah dalam Pengambilan Keputusan di SDN 004 Teluk Durian (Kepulauan Anambas) - Wildansyah Lubis; Winara Winara; Sartika Sari Sinaga; Veronika Banjarnahor; Esra Theresia Sinambela (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
In a school, the most crucial decision-maker is the principal. The principal as the main leader has the responsibility to direct, improve and manage the quality of education of the school he leads in accordance with the vision and mission of the school. Many cases that occur in schools discuss the role of the principal as the highest leader in the school in making decisions for mutual progress. The purpose of this study is to identify cases that are ethical dilemmas at SDN 004 Teluk Durian to find out the methods/steps/procedures carried out by the principal of SDN 004 Teluk Durian in making decisions, to find out the challenges faced in decision-making in cases of ethical and disciplinary dilemmas, to find out the factors that facilitate or help the principal of SDN 004 Teluk Durian in making decisions. This study uses literature study research, by conducting an analysis by comparing the results of previous research through journals that are relevant to the study of the problem being studied. The subject of this research is the principal at SDN 004 Teluk Durian, Anambas Islands Regency, Riau Islands Province. From the results of the research that has been carried out, it was found that Mr. Muhammad Rauf, S.Pd.SD as the principal of SDN 004 Teluk Durian, the methods/procedures/steps carried out in decision-making consist of several ways, namely (1) Identifying problems, (2) classifying problems, and (3) Practice decision-making. The principal also makes decisions that are in line with the knowledge of 4 paradigms, 3 principles and 9 steps of testing and has a paternalistic type of democratic leadership style. Several efforts made by Mr. Muhammad Rauf, S.Pd.SD as the principal at SDN 004 Teluk Durian in implementing the code of ethics at school for the problem of late attendance at school, students were sanctioned and in line with the violations that had been committed. The challenge faced by the principal of SDN 004 Teluk Durian is that the local culture of the school is still very thick, such as the use of Indonesian language is very minimal in school and the use of technology in accordance with the development of the times is still relatively low so that it is not able to compete with schools in urban areas. The conclusion of this study is that Mr. Muhammad Rauf, S.Pd.SD as the principal of SDN 004 Teluk Durian, the methods/procedures/steps carried out in decision-making are in line with the knowledge of 4 paradigms, 3 principles and 9 testing steps and have a paternalistic type of democratic leadership style.